A UK Operational Practitioner View – some Challenges of Health Informatics are Trans-national - Roberts, J. (Methods of Information in Medicine, 2002)
Objective: To explore the relevance of catalysts and inhibitors to the achievement of an inclusive identity for health informatics; particularly from an operational perspective in the UK.Methods: Consideration of the different dimensions of health informatics, as practised in a working healthcare delivery environment; specifically commenting on the synergy and disjunctions with academic and scientific practitioners in the same domain.Results and Conclusions: There appear to be common ground and internationally applicable issues across the domain. Recognising the differences and similarities will contribute towards harmonisation of the field and its ultimate elevation to a mature discipline and profession.
Keywords: Healthcare delivery; health informatics; identity crisis; fragmentation; synergy